2022
DOI: 10.3390/biomedicines10061357
|View full text |Cite
|
Sign up to set email alerts
|

Rac1 as a Target to Treat Dysfunctions and Cancer of the Bladder

Abstract: Bladder pathologies, very common in the aged population, have a considerable negative impact on quality of life. Novel targets are needed to design drugs and combinations to treat diseases such as overactive bladder and bladder cancers. A promising new target is the ubiquitous Rho GTPase Rac1, frequently dysregulated and overexpressed in bladder pathologies. We have analyzed the roles of Rac1 in different bladder pathologies, including bacterial infections, diabetes-induced bladder dysfunctions and bladder can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 143 publications
1
2
0
Order By: Relevance
“…This study conducted a comprehensive analysis of the expression patterns of RAC1 at the pan-cancer level and its relationship with cancer progression, prognosis, immune microenvironment, and drug sensitivity. Our findings echo previous studies that have revealed the important role of RAC1 in various cancers, particularly in regulating cell migration, proliferation and survival 5,[30][31][32] . Furthermore, our research extends the understanding of RAC1 as a prognostic biomarker, further revealing that high expression of RAC1 is associated with reduced B cell infiltration.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study conducted a comprehensive analysis of the expression patterns of RAC1 at the pan-cancer level and its relationship with cancer progression, prognosis, immune microenvironment, and drug sensitivity. Our findings echo previous studies that have revealed the important role of RAC1 in various cancers, particularly in regulating cell migration, proliferation and survival 5,[30][31][32] . Furthermore, our research extends the understanding of RAC1 as a prognostic biomarker, further revealing that high expression of RAC1 is associated with reduced B cell infiltration.…”
Section: Discussionsupporting
confidence: 91%
“…Rac1 is commonly characterized by its heightened expression and/or enhanced activity in a spectrum of solid malignancies, such as bladder 5 , and hepatocellular carcinomas 6 . At the same time, RAC1 is also closely related to tumour metastasis 7 .…”
Section: Introductionmentioning
confidence: 99%
“…High expression of EGFR has been observed in human tumors (e.g., the lung and pancreas) associated with a poor prognosis. EGFR activation leads to the induction of the small GTPase Rac1-GTP form in the cytosol, causing actin organization, lamellipodia extensions, and macropinocytotic cellular uptake. ,, In this study, human epidermoid carcinoma-derived A431 cells with high EGFR expression on the plasma membrane (∼10 6 receptors/cell) , were used for assessing macropinocytosis induction and cellular MV uptake.…”
Section: Resultsmentioning
confidence: 99%